(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This study investigates the prevalence of elevated uric acid levels (hyperuricemia) among young individuals and its impact on kidney function. Hyperuricemia, even in asymptomatic cases, can serve as an early marker of metabolic disturbances and subclinical renal dysfunction. The findings highlight the distribution of hyperuricemia in youth, the contributing factors, and emphasize the need for preventive measures and lifestyle interventions. The results are important for developing strategies aimed at preserving kidney health and reducing the risk of chronic diseases in young populations.